Mild cycles open closed communities to ecological restoration. Issue 4 (2nd March 2020) - Tielke, Ann‐Kathrin; Karreman, Japke; Vos, Matthijs
Abstract : Species loss is a global issue. With up to a million species at risk and insufficient protected area to maintain the world's biodiversity, humanity will increasingly need to rely on species re‐introductions to locally restore diversity and function. However, such restoration attempts are bound to fail when ecological communities get locked in a closed state that is resistant to recovery. It is presently unknown how to repair these closed systems. We use mathematical models to identify ways out of this problem. We first show how ecological communities may enter a closed state, to then explain how to open them up again for restoration of their original diversity. We find that restoration is often still possible shortly after initial species loss, as (1) the secondary extinctions that produce closure have not happened yet and (2) mild population fluctuations still allow successful repair during a transient postdisturbance phase. However, after this typically short window of opportunity for restoration, the system enters a new equilibrium, which may be a closed state. Our analysis shows how to take ecological communities out of the closed state: Appropriate management of carrying capacities produces a regime of mild population fluctuations that opens a window for successful species re‐introductions. These windows can be perpetually recurring or permanently open. Such opportunities for repair can be absent under regimes of wild cycles or perfect stability. We conclude that mild cycles may open windows of opportunity for the repair of communities that have become resistant to recovery.